Emotional, sensory, and social dimensions of consumer buying behavior - Soares, Ana Maria, 1968-; Elmashhara, Maher Georges, 1984- (Advances in marketing, customer relationship management, and e-services (AMCRMES) book series., 2020)
"This book explores the importance of the emotional side of shopping and discusses shopper behavior influences in a highly competitive, changing, and challenging retail industry"--